3D fabric dynamic simulation based on Mapreduce. Issue 6 (2nd November 2015) - Shi, Hengliang; Bai, Xiaolei; Duan, Jianhui
Abstract : Purpose: – In cloth animation field, the collision detection of fabric under external force is very complex, and difficult to satisfy the needs of reality feeling and real time. The purpose of this paper is to improve reality feeling and real-time requirement. Design/methodology/approach: – This paper puts forward a mass-spring model with building bounding-box in the center of particle, and designs the collision detection algorithm based on Mapreduce. At the same time, a method is proposed to detect collision based on geometric unit. Findings: – The method can quickly detect the intersection of particle and triangle, and then deal with collision response according to the physical characteristics of fabric. Experiment shows that the algorithm improves real-time and authenticity. Research limitations/implications: – Experiments show that 3D fabric simulation can be more efficiency through parallel calculation model − Mapreduce. Practical implications: – This method can improve the reality feeling, and reduce calculation quantity. Social implications: – This collision-detection can be used into more fields such as 3D games, aero simulation training and garments automation. Originality/value: – This model and method have originality, and can be used to 3D animation, digital entertainment, and garment industry.